Imperatorin alleviates the abnormal proliferation, migration, and foaming of ox-LDL-induced VSMCs through regulating PI3K/Akt/mTOR signaling pathway. (July 2020) - Li, Wenqi; Niu, Xinyi; Yu, Jinjin; Xiao, Xin; Zang, Lulu; Zhao, Jinmeng; Huang, Qiuxia; Li, Weifeng
Graphical abstract: Highlights: IMP regulates cell cycle of ox-LDL-stimulated VSMCs. IMP reduces intracellular lipid accumulation and slows foaming process of VSMCs. IMP attenuates expressions of PCNA, MMP-2 and LOX-1 in ox-LDL-induced VSMCs. IMP mitigates VSMCs proliferation, migration and foaming by inhibiting PI3K/Akt/mTOR pathway. Abstract: Abnormal proliferation, migration and foaming of vascular smooth muscle cells (VSMCs) are involved in atherosclerosis (AS) process. Imperatorin (IMP) is a coumarin compound mainly originated from angelica dahurica in natural plants. In this study, effects of IMP on proliferation, migration and foaming of oxidized low-density lipoprotein (ox-LDL)-induced VSMCs were investigated. The results showed that IMP regulated cell cycle in S G2/M phase and down-regulated the proliferating cell nuclear antigen (PCNA), and then exerted anti-proliferation effect. IMP might have a repressive effect on migration in ox-LDL-stimulated VSMCs through inhibiting the metalloproteinase-2 (MMP-2). Oil red O staining showed IMP suppressed lipid accumulation in ox-LDL-induced-VSMCs. This was consistent with the determination of Lectin-like oxidation of lectin-like ox-LDL receptor-1 (LOX-1) and total cholesterol (TC). IMP also reduced the expression of p-PI3K, p-Akt and p-mTOR in ox-LDL-treated VSMCs. These results suggested that IMP might play an anti-lesion role in ox-LDL-stimulated-VSMCs by inhibiting the PI3K/Akt/mTOR pathway.